Protocolos de extraccion de ADN en sangre de cerdos criollos en Quevedo. - Vidal Vera, Frank Willian (2015)
An investigation whose purpose was to conduct a DNA extraction protocol in national creole pigs with a high degree of purity and concentration, to obtain molecular markers designed to show its potential in production arises. DNA extraction from blood involves the use of complex methodologies due to problems such as degradation, limiting amounts of DNA and the presence of inhibitors that may be co-extracted DNA. In the Laboratory of Biotechnology of the State Technical University Quevedo has hindered the standardization of a useful DNA extraction and analysis of quality and quantity protocol. In order to find a method which provides the best conditions of extraction, purification and DNA amplification methodologies comparing two DNA extraction from peripheral blood, including salting out method was performed, and method TENS are currently used in the laboratory, allowed obtaining DNA quality and purity required for PCR amplification from blood volumes, with a minimum volume of 100 mL starting blood. Furthermore methodologies electrophoresis and spectrophotometry were used to evaluate the quality and quantity of extracted DNA, achieving determine the best method for extracting DNA T5. In conclusion by the two methodologies for DNA quantification, it was determined that the salting out, which was based on the extraction of DNA with phenol, chloroform and isoamyl alcohol was the best method for extracting DNA, obtaining good yields and quality. Keywords: Blood samples; DNA extraction; salting-out; PCR, TENs.